MMP-9-Related microRNAs as Prognostic Markers for Hemorrhagic Transformation in Cardioembolic Stroke Patients - Zheng, Lukai; Xiong, Yao; Liu, Junfeng; Yang, Xue; Wang, Lu; Zhang, Shuting; Liu, Ming; Wang, Deren (Frontiers in Neurology, 2019)
Studies suggest that microRNAs that regulate expression of matrix metalloproteinase (MMP)-9 may be involved in hemorrhagic transformation (HT) after cardioembolic stroke, so we examined whether such microRNAs could predict HT in acute cardioembolic stroke patients. Blood samples were prospectively collected from patients who later experienced HT (n =29) or did not (n =29), and the samples were assayed for eight microRNAs identified as related to MMP-9 based on three microRNA databases. Expression levels of these microRNAs were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) in 28 of the 58 patients, 14 of whom suffered HT and 14 of whom did not. Four differentially expressed miRNAs were identified: hsa-miR-21-5p, hsa-miR-206, hsa-miR-491-5p and hsa-miR-3123. Subsequent qRT-PCR analysis of these four miRNAs across all 58 patients showed that levels of miR-21-5p, miR-206, and miR-3123 were significantly higher in patients with HT than in those without HT, while expression of miR-491-5p was similar between the two groups. The area under the receiver operating characteristic curve for predicting HT was 0.677 (95% CI 0.535-0.818) for miR-21-5p, 0.687 (95% CI 0.543-0.830) for miR-206, and 0.661 (95% CI 0.512-0.810) for miR-3123. Our results suggest that these three microRNAs may be prognostic markers for HT after cardioembolic stroke, which should be verified by future studies with large samples.